FAMILY SUPPORT TO CLIENTS OF COVID-19 SURVIVORS SANTA ELISABETH HOSPITAL MEDAN - Maria Pujiastuti; Vina Yolanda Sigalingging; Henry Eduwar Siregar (HealthCare Nursing Journal, 2022)
The purpose of this study was to determine the description of family support for clients who survived COVID-19 at Santa Elisabeth Hospital Medan in 2021. This research was quantitative descriptive. The subjects in this study were 30 people who were obtained through purposive sampling technique using the Vincent formula. The data collection technique is a questionnaire via google form. The questionnaire contains questions about the description of family support on indicators emotional/hope support, instrumental/real support, and information/knowledge support. The results of the study found that: a) descriptions of emotional/hope support in sufficient category 21 people (70%), instrumental/real support in good category 28 people (93%), information/knowledge support with good category 20 people (66%). So that in general the description of family support for clients who have survived COVID-19 at the hospital. St Elisabeth Medan 2021 is a good category of 62%